High Pressure Processing of Food Principles, Technology and Applications - Balasubramaniam, V.M; Barbosa-Cánovas, Gustavo V.; Lelieveld, Huub L.M (Food Engineering Series, 2016)
High-pressure processing (HPP) represents an industrially relevant solution to the growing consumer demand for wholesome, fresh-tasting foods, where application of pressure assures food safety. Through 31 chapters grouped into 7 relevant sections, the book comprehensively reviews and summarizes current state-of-the-art knowledge, from process engineering, packaging, industrial scale equipment, consumer acceptance, regulations, to application of high pressure in food pasteurization, sterilization, extraction, homogenization, and freezing and thawing. Food safety specialists and process authorities working in both government and food industry sectors will find useful chapters about pressure effects on harmful biological agents as well as approaches to validation of high pressure technology.  Chapters related to high pressure reaction kinetics, process uniformity, mathematical modeling, pressure effects on proteins, enzymes starch and bioactive co mpounds, and structural changes in pressure treated foods will be particularly beneficial for graduate and undergraduate students to discover the latest information on high pressure preservation principles. Chapters concerning high pressure applications in different food industry sectors will serve as excellent reference to food industry professionals, in particular to those involved in the processing of products such as meat, seafood, beverage, dairy, eggs, fruits and vegetable products. .